The Productive Role Of Fisher Women In Strengthening The Fisheries Household Economy In Seruyan District - Lili Winarti; Rokman Permadi (AGRIBEST, 2020)
Women fishermen or fishermen's wives in the invited river villages work, with the aim of increasing income and helping the household economy. The purpose of this study is to identify the productive work of women fishermen in fishing activities, analyze the level of household income of capture fishermen, and analyze the contribution of fishermen women's income to their household income. This research was carried out in Sungai Undang Village, respondents in this study were fishermen and his wife who were actively working in the fisheries sector. The research method was carried out using a survey of 85 selected respondents, then tabulated and calculated their income and contribution. The results of this study are the majority of women fishermen in Sungai UU Village work as shrimp head cutting laborers with a percentage of 42%, salted fish craftsmen by 32%, fish vendors by 16% and ebi shrimp craftsmen, shrimp paste, cencalu 4%, Analysis of income level fisherman households originating from the income of the wife and husband, where the level of income of women fishermen ranges from Rp 315,946 to Rp 1,575,714 and the husband's income still exceeds the wife's income which ranges from Rp 2,139,286 to Rp 3,270,270, and the role contribution by the biggest fisherman women in activities carried out by salted fish artisans with a contribution of 42.4%, fish hawkers by 25.9%, ebi-cincalu shrimp craftsmen by 17.4% and the smallest contribution was laboring shrimp head cutters and fish handlers with contribution of 8.8%, this shows that even the smallest amount of work done by women fishermen is able to m increase and contribute to household income.